Anatomy of visualizations in data journalism: The cases of Spain and the United States - Córdoba-Cabús, Alba; López-Martín, Álvaro (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
This paper examines the data visualizations incorporated in the online versions of the main hybrid newspapers in Spain and the United States to find out their features and the role they play in the articles. In addition to this objective, the aim is to determine whether there are significant differences in the use of visualizations in the practice of data journalism in national and foreign newspapers. Through a content analysis, the articles published during the year 2021 in the web versions of El País, El Mundo, The New York Times and The Washington Post were analyzed.